Carbonaceous nanostructured materials: obtaining, agents dopants and electrochemical applications - Rodríguez-Suarez, Norberto; Quesada-González, Omaida; Danguillecourt-Álvarez, Edelio; Almenares-Verdecia, Isabel (Revista Cubana de Química, 2021)
Carbonaceous materials are currently of great importance because they are used in electrochemical devices capable of storing energy from renewable sources of electricity generation. In this work, a search on the characteristics of precursors, synthesis methods and characterization of carbonaceous materials with electrochemical applications was carried out. As a result of this review is obtained that distillery vinasse and torula liquor are potential sources of carbon for the synthesis of those materials. Also those synthesis methods using templates lead to improved electrical properties, clays are the most commonly used templates for synthesis, but it is evidenced the possibility of using zeolites chemically modified with these ends. The doping with nitrogen, phosphorus and some metal oxides leads to an improvement of the electrical properties of the obtained materials.